Assessing the Influence of Environmental Factors on Landslide Frequency and Intensity in Northwestern Sichuan, SW China, Using Multi-Temporal Satellite Imagery - Yu Zhu; Huajin Li; Ran Tang; Zhanfeng Fan; Lixuan Mao; Yifei Lu; Chuanhao Pu; Yusen He (Remote Sensing, 2025)
Landslides are a significant geological hazard with substantial socio-economic and environmental consequences, particularly in northwestern Sichuan, SW China, where complex geological and climatic conditions contribute to their occurrence. This study examines 1629 recorded landslide events, including 240 active landslides that have undergone substantial changes over the past two decades. By analyzing multi-temporal satellite imagery, this research investigates the relationship between landslide occurrence and key environmental factors such as annual rainfall and the Normalized Difference Vegetation Index (NDVI). The results reveal that landslides are most frequent on southwest-, south-, east-, and southeast-facing slopes, where the Föhn effect interacts with rainfall and vegetation patterns, thereby increasing landslide susceptibility. Rainfall intensity is identified as a critical factor, with landslide areas expanding significantly when annual rainfall exceeds 650 mm, while minimal changes are observed when rainfall is below 550 mm. The relationship between the NDVI and landslide occurrence is non-linear; higher vegetation cover does not necessarily correlate with reduced landslide frequency. Notably, landslide expansion is more pronounced when NDVI values are below 0.82, with a suppression effect occurring beyond this threshold. A threshold model based on the interaction between the NDVI and rainfall provides valuable insights into landslide dynamics, offering a framework for improved risk management. Slope characteristics are crucial in landslide evolution, with steeper slopes leading to greater vertical drops and more frequent events, making slope zone identification key for predicting future expansion.